Improving Discovery and Use of NASA's Earth Observation Data Through Metadata Quality Assessments. (28th April 2021) - Bugbee, Kaylin; le Roux, JeannÉ; Sisco, Adam; Kaulfus, Aaron; Staton, Patrick; Woods, Camille; Dixon, Valerie; Lynnes, Christopher; Ramachandran, Rahul
High quality descriptive metadata is essential to enabling the effective discovery of Earth observation data to a growing number of diverse users. In this paper, we define a framework to assess the quality of NASA's Earth observation metadata with the overarching goal of improving the discoverability, accessibility and usability of the data it describes. The framework, developed by the Analysis and Review of the Common Metadata Repository (ARC) team, focuses on the metadata quality dimensions of correctness, completeness, and consistency. The methodology used by the ARC team to implement the framework is described, as well as best practices, lessons learned and recommendations for implementing similar metadata quality assessment processes. Initial results from the project indicate that this methodology, in combination with community and stakeholder collaboration, is effective in improving metadata quality.